Analisa Merancang Sistem Informasi Monitoring Perkembangan Proyek - Riski Annisa; Firly Annisa Luthfi (Jurnal Informatika Kaputama (JIK), 2023)
PT. Permata Trikarya Utama is a company engaged in Design Engineering and Construction Management consulting services. Judging from the monitoring system and also sending reports and filing report files which are still running manually, these are the main problems that need to be addressed in this company. To facilitate the current process, the author tries to design a web-based system regarding the monitoring system at PT. Permata Trikarya Utama. The design of this information system is a good solution to help solve the problems that exist in the company. In designing this monitoring system using the waterfall method with stages, namely software requirements analysis, design, implementation and testing. With a monitoring system design that can create and archive reports, display schedules, and manage project and employee data, which will make it easier for companies to manage data and monitor project progress and archive existing files. So that companies can more easily monitor developments that occur in projects and archive files or progress files.